Migration distance is a fundamental axis of the slow-fast continuum of life history in boreal birds. Issue 4 (7th July 2021) - Winger, Benjamin M; Pegan, Teresa M
Abstract: Seasonal migration is intrinsically connected to the balance of survival and reproduction, but whether migratory behavior influences species' position on the slow-fast continuum of life history is poorly understood. We found that boreal-breeding birds that migrate long distances exhibit higher annual adult survival and lower annual reproductive investment relative to co-distributed boreal species that migrate shorter distances to winter closer to their breeding grounds. Our study uses "vital rates" data on reproductive output and survivorship compiled from the literature for a species assemblage of 45 species of mostly passerine birds. These species breed sympatrically in North American boreal forests but migrate to a diversity of environments for the northern winter. After controlling for body size and phylogeny, migration distance and apparent annual adult survival are positively related across species. Both migration distance and survival are positively correlated with wintering in environments that are warmer, wetter, and greener. At the same time, longer migrations are associated with reduced time spent on the breeding grounds, lower clutch sizes, and lower fecundity (clutch size × maximum number of broods per year). Although seasonal migration is often associated with high mortality, our results suggest that long-distance migration imposes selection pressures that both confer and demand high adult survival rates. That is, owing to the reproductive cost of long-distance migration, this strategy can only persist if balanced by high adult survival. Our study supports the idea that migration evolves to promote survival of species breeding in seasonal environments. In boreal birds, the evolution of the longest migrations yields the highest survival, but at an inherent cost to annual fecundity. Our results therefore reveal migratory distance as a fundamental axis of the slow-fast continuum that predicts, and is inextricable from, the balance of survival and reproduction. Graphical Abstract: Lay Summary: A trade-off between investment in survival and reproduction is among the most fundamental patterns in nature. Seasonal migration allows animals to move between areas used specifically for reproduction or survival. Migration is frequently thought to involve high mortality, suggesting that the longest-distance migrations should be costliest to survival. We show that, counterintuitively, birds that breed in boreal North America and migrate long distances for the winter are more likely to survive to the following year than birds that migrate shorter distances. Long-distance migrants also lay fewer eggs each year than short-distance migrants. Our study reveals how the evolution of a remarkable behavioral adaptation—long-distance migration— simultaneously shapes and is shaped by the fundamental balance of reproduction and survival.